MYC and BCL2 protein expression predicts survival in patients with diffuse large B‐cell lymphoma treated with rituximab. (8th February 2014) - Perry, Anamarija M.; Alvarado‐Bernal, Yuridia; Laurini, Javier A.; Smith, Lynette M.; Slack, Graham W.; Tan, King L.; Sehn, Laurie H.; Fu, Kai; Aoun, Patricia; Greiner, Timothy C.; Chan, Wing C.; Bierman, Philip J.; et al.
Summary Diffuse large B‐cell lymphoma (DLBCL) is a heterogeneous disease and "double‐hit" DLBCL, with both MYC and BCL2 translocations has a poor prognosis. In this study, we investigated whether MYC and BCL2 protein expression in tissue would predict survival in DLBCL. The study included 106 cases of de novo DLBCL treated with rituximab and cyclophosphamide, doxorubicin, vincristine and prednisone (R‐CHOP) or CHOP‐like regimens. The results were validated on an independent cohort of 205 DLBCL patients. Patients with low expression of BCL2 (≤30%) and MYC (≤50%) had the best prognosis, whereas those with high BCL2 (>30%) and MYC (>50%) had the worst outcome. In multivariate analysis, the combination of the BCL2 and MYC was an independent predictor of overall survival (OS) and event‐free survival (EFS) (P = 0·015 and P = 0·005, respectively). The risk of death was nine times greater for patients with high BCL2 and MYC compared to those with low expression. High BCL2 and MYC was a strong predictor of poor OS (P < 0·001) and EFS (P = 0·0017) in patients with the germinal centre B‐cell (GCB) type, but not in the non‐GCB type. In DLBCL, high co‐expression of MYC and BCL2 was an independent predictor of poor survival, and could be used to stratify patients for risk‐adapted therapies.